2012
DOI: 10.1177/2158244012436563
|View full text |Cite
|
Sign up to set email alerts
|

Black Teenage Pregnancy

Abstract: This article examines the relative importance of race and socioeconomic status (SES) in determining whether Black and White teenagers report having ever been pregnant. Data gathered from 1999 to 2006 by the National Center for Health Statistics of the Center for Disease Control and Prevention included 1,580 Black and White females aged 15 to 19 years. Results supported the effects of race and SES, with SES having the stronger effect. However, the effects of race and SES differ when controlling for the state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We will include studies of all designs (qualitative, quantitative and mixed methods) that examine TPI among ACB adolescents within North America, and grey literature including preprint conference abstracts, editorials, among others, found to be pertinent in addressing the research question. We will exclude studies not written in English, articles published before 2010 (this timeline was chosen to include more recent literature), articles whose primary focus or outcome is not teen pregnancy, studies Open access with less than 50% ACB population, studies whose age range overlaps with our intended age range for the study (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in ways that we are unable to separate out or glean results for each age group. Finally, given our focus on TPI, we will review all available evidence from studies conducted on adolescent girls, adolescent boys and/or both.…”
Section: Type Of Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…We will include studies of all designs (qualitative, quantitative and mixed methods) that examine TPI among ACB adolescents within North America, and grey literature including preprint conference abstracts, editorials, among others, found to be pertinent in addressing the research question. We will exclude studies not written in English, articles published before 2010 (this timeline was chosen to include more recent literature), articles whose primary focus or outcome is not teen pregnancy, studies Open access with less than 50% ACB population, studies whose age range overlaps with our intended age range for the study (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in ways that we are unable to separate out or glean results for each age group. Finally, given our focus on TPI, we will review all available evidence from studies conducted on adolescent girls, adolescent boys and/or both.…”
Section: Type Of Sourcesmentioning
confidence: 99%
“…Most pregnancy prevention programmes have focused on addressing parental involvement and the teen’s perceived social expectations of early childbearing,9 with only a few studies focusing on possible disparities that may exist across races and the associated factors. Available evidence acknowledges the importance of investigating the disparities in teen pregnancy problem that exists among ACB populations compared with other racial groups,10 11 with particular attention being paid to socioecologic factors such as the individual’s identities (eg, age, gender, etc), socioeconomic status, psychosocial vulnerabilities (eg, discrimination based on race, gender),10 11 among others. Furthermore, given that an apparent gap exists in the teen pregnancy discourse for adolescent men, and the ACB population.…”
Section: Introductionmentioning
confidence: 99%
“…Racial/ethnic minority youth are more likely to live in poverty than White youth, and poverty is a major predictor of teen pregnancy (e.g., Su & Addo, 2018) beyond race. Winters and Winters (2012) found that during good economies, the variation in teen pregnancy was the result of socioeconomic status alone. Black youth were more likely than White youth to experience teen pregnancy only when the economy was in a downturn.…”
Section: Theoretical Background and Conceptual Model For Present Studymentioning
confidence: 99%
“…Many unmarried adolescent mothers live in impoverished neighborhoods and the likelihood that their children will grow up in poverty is high (Domenico & Jones, 2007). For some African American female teens, becoming pregnant is a way to become a woman when they are faced with few educational and job opportunities (Winters &Winters, 2012). In addition, teen pregnancy is more likely to be peer accepted in poor neighborhoods (Winters &Winters, 2012).…”
Section: Poverty and Teen Pregnancymentioning
confidence: 99%